Field notes contributed by James J. Dinsmore and Stephen J. Dinsmore, fall 1984 - Dinsmore, James J.et al; Dinsmore, Stephen J.et al (1984)
Field notes were contributed by James J. Dinsmore and Stephen J. Dinsmore, fall 1984, along with a cover letter from James J. Dinsmore to Michael C. Newlon related to various enclosures, November 28, 1984. The field notes listed 100 bird species sighted by ten observers in 22 locations. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed